(untitled) (Eurasian Journal of Engineering and Technology, 2023)
Sand concentrator methods are a means of preparing laboratory models for carrying out many geotechnical experiments. This study used five methods to determine the highest sand density. A series of practical tests were conducted to evaluate the performance of each method used, and they gave acceptable results in the test. After the single experiment in the laboratory work site, the highest density was 18.5kN/m3 When using the vibrating technique. The lowest density was with the direct soil filling method, which was 15.47 kN/m3. These methods are only for comparison because the soil in them is loose. Where other methods proved their efficiency in working, the density was 16.37 kN/m3 at sand pluviation. And 16.7 kN/m3 at sand hopper. The last one is 16.8 kN/m3 at sand suppression. It can be said that the best method is the vibrating method because it gives the highest results